2018
DOI: 10.1016/j.ijmultiphaseflow.2017.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Air-water flow properties in stepped chutes with modified step and cavity geometries

Abstract: Skimming air-water flow properties were investigated in a stepped chute configured with triangular steps, chamfered steps, and partially blocked step cavities. The turbulent interactions between air and water were examined using a synchronised system consisting of a dual-tip phase-detection probe and a pressure transducer mounted side-by-side. In comparison to uniform triangular steps, the chamfered steps were found to cause a reduction in air entrainment and an increase in mean velocity gradient next to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The stepped spillways are generally uniform in width along the flow channel. With increasing discharge, three distinct flow regimes of nappe, transition and skimming have been found, and their flow performances, energy dissipation efficiencies, pressure characteristics and air-water flow properties have been thoroughly investigated [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The stepped spillways are generally uniform in width along the flow channel. With increasing discharge, three distinct flow regimes of nappe, transition and skimming have been found, and their flow performances, energy dissipation efficiencies, pressure characteristics and air-water flow properties have been thoroughly investigated [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and Chanson examined the air-water properties on a stepped spillway with modified steps and cavities [5]. It was concluded that partial cavity blockages have little effect on air entrainment, but were linked to an increased presence of large-scale structures in the overflow.…”
Section: Introductionmentioning
confidence: 99%
“…Flows on stepped chutes are characterized by strong energy dissipation and complex interactions between air and water entities within the flows downstream of the inception point of free-surface aeration (e.g. Gonzalez and Chanson, 2008;Bung and Valero, 2016;Felder and Chanson, 2016a;Zhang and Chanson, 2018). Stepped spillways for flood mitigation purposes are typically designed for maximum flow conditions, which take place in the skimming flow regime.…”
Section: Introductionmentioning
confidence: 99%